EFFECTS OF PHYSICAL EXERCISE DURING HOSPITALIZATION IN CHILDREN AND ADOLESCENTS WITH CANCER: A SYSTEMATIC REVIEW - Scárlat da Silva Santos; Luciane Dalcanale Moussalle; João Paulo Heinzmann-Filho (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To identify the effects of exercise programs during hospitalization on children and adolescents with cancer. Data source: This is a systematic review, carried out in PubMed/ Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library Online (SciELO), Latin American and Caribbean Center on Health Sciences Information (BIREME), and Physiotherapy Evidence Database (PEDro). We selected studies that included children and adolescents diagnosed with cancer (solid or hematologic) and submitted to exercise protocols during hospitalization. Studies involving patients with other pathologies or with a medical contraindication for exercise were excluded. We used the following search strategy: Neoplasm OR Leukemia OR Cancer OR Tumor OR Medical Oncology AND Hospitalization OR Inpatient Care Units OR Intrahospital AND Exercise. The methodological quality of the studies was analyzed by the PEDro scale. Data synthesis: Among the 626 articles found, only 9 fulfilled the inclusion criteria, obtaining a regular methodological quality. The samples had 172 participants, aged 4 to 18 years. Only 6 studies presented both intervention group and control group. The intervention group received strength, aerobic, and muscle stretching exercises, and games, among others. The control group received the standard treatment. The studies varied regarding time, frequency, intensity, and type of exercise. Most studies showed an increase in muscle strength (4/5), followed by an improvement in physical fitness (2/3) and functional capacity (2/4). No adverse events were reported during the interventions. The methodological quality was considered regular. Conclusions: The findings suggest that. during hospitalization of children and adolescents with cancer, exercise improves muscle strength, physical fitness, and functionality.